FAMILY’S RESILIENCE SPIRIT PEOPLE WITH MENTAL ILLNESS AMONG BALINESE CULTURE - Putro, Bambang Dharwiyanto (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Families who have family members of people with mental disorders experience a heavy burden and various forms of stress that make this condition difficult to deal with. This is influenced by social isolation, stigmatization and psychological burdens and increasing economic burdens. On the other hand the family still hopes that patients can recover completely. A person who is able to survive in these difficult conditions is called a person who has resilience. Resilience is seen as a personal quality that involves a high degree of adaptability and flexibility when faced with pressure, both internal and external, but also in the end they can become stronger than before. In Bali, according to the belief of Balinese who are Hindus, there is a concept that healthy sickness occurs when there is no balance of the three elements, namely Buana Alit , Buana Agung and Sang Hyang Widhi Wasa as sekala or niskala factors that can cause interference in humans. This belief is what causes the sufferer or family to visit a shaman or balian to get directions or treatment. Likewise, after the patient is discharged from the hospital, most sufferers go to the doctor and courtroom, and there are more often to the courtroom or doctor alone. If they relapse, most come to balian.Balian is able to influence patients and their families and most believe in what is stated balian . It can be seen that the role of Balinese culture, especially in relation to mental disorders, needs special attention. The writing of this article would like to show recommendations for potential treatments that can help in the healing or recovery stage at least as an additional experience.